Chemoradiation-Induced Superior Vena Cava Syndrome: A Case Report - Mathieu Castonguay; George Rodrigues; Mark Vincent; Richard A Malthaner; Lin-Ruo Guo (Canadian Respiratory Journal)
A case of a 54-year-old man who developed superior vena cava syndrome secondary to vascular fibrosis, 30 months after radical chemoradiation for stage III non-small cell lung cancer, is presented. The literature regarding the etiology, diagnosis and treatment of this rare entity is discussed.